Figure 3 from: Potapov G, Kondakov A, Kolosova Y, Tomilova A, Filippov B, Gofarov M, Bolotov I (2018) Widespread continental mtDNA lineages prevail in the bumblebee fauna of Iceland. ZooKeys 774: 141-153. https://doi.org/10.3897/zookeys.774.26466 - Potapov, Grigory S.; Kondakov, Alexander V.; Kolosova, Yulia S.; Tomilova, Alena A.; Filippov, Boris Yu.; Gofarov, Mikhail Yu.; Bolotov, Ivan N. (Zenodo, 2018)
Figure 3 Approximate distribution ranges of the widespread ubiquistic COI lineages recorded in bumblebee populations from Iceland (see Suppl. material 1 for details). Northern range boundaries of Bombus lucorum and B. hortorum lineages are in accordance with published sources (Williams et al. 2012, Kolosova et al. 2016, Potapov and Kolosova 2016). The map was created using ESRI ArcGIS 10 software (www.esri.com/arcgis). The topographic base of the map was created with Natural Earth Free Vector and Raster Map Data (www.naturalearthdata.com).